Pengaruh Konten TikTok @pandawaragroup Terhadap Perilaku Zero Waste Pengikutnya - Yumna, Salsabila; Dharta, Firdaus Yuni; Susanto, Tri (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
The background of this research is the large amount of plastic waste that has not been managed properly, thus there is a need for media intervention to influence the community to reduce plastic waste. Content promoted on social media, especially TikTok, can serve as a medium to educate the public about environmental issues occurring in Indonesia. This study aims to determine the extent of the influence of TikTok content exposure from Pandawara Group on its followers' zero-waste behavior, assessed through frequency, intensity, and duration. This research employs a descriptive quantitative method with questionnaires as the research instrument. The population of this study is a 11.9 million followers of the TikTok account Pandawara Group. A total of 100 respondents were selected as the sample, using Slovin's formula. The results of the study prove that In the frequency and intensity variables there was a significant influence while the duration variable had no effect, Next, based on the results of the determination coefficient test, the R-Square value found was 0.181. So, it can be concluded that 18% of the zerowaste behavior of Pandawara Group followers is influenced by exposure to TikTok content @pandawaragroup.